Rapid and Precise Approaches for XRF Analysis of Rare Earth Niobates - Alexandra Alexandrovna Arkhipenko; Galina Evgenievna Marina; Mikhail Alexandrovich Ryumin; Marina Sergeevna Doronina; Natalia Alexandrovna Korotkova; Tatiana Dmitrievna Ksenofontova; Vasilisa Borisovna Baranovskaya (Analytica)
This work describes a two-stage technique of X-ray fluorescence (XRF) analysis of rare earth niobates. A comparison between the two approaches revealed that the Fundamental Parameters Method (FPM) can be employed for a rapid preliminary assessment of the composition of the resulting material and the construction of calibration curves can be used to determine the contents of the major elements with precision. The results of the relative standard deviation (RSD) for FPM were no more than 7%, while the approach to construct calibration curves had an RSD of no more than 1%. Calibration samples were prepared using the same synthesis method as the study samples to construct the calibration curves. The possibility of constructing calibration dependencies using mixtures of oxides was assessed, but this approach could not provide the desired accuracy. The obtained results have been shown to have a good correlation with inductively coupled plasma optical emission spectrometry. The developed technique enables the determination of the major components in niobates containing two and three rare earth elements, which are used as optical materials and medium-entropy ceramics.